a)
f(x) = 2x² + 8x + 6
a = 2, b = 8, c = 6
∆ = 8² - 4 * 2 * 6 = 64 - 48 = 16
√∆ = 4
x = (-8 - 4)/4 = -3
x = (-8 + 4)/4 = -1
b)
f(x) = x² - 5x + 6
a = 1, b = -5, c = 6
∆ = (-5)² - 4 * 1 * 6 = 25 - 24 = 1
√∆ = 1
x = (5 - 1)/2 = 2
x = (5 + 1)/2 = 3
c)
f(x) = x² + x - 20
a = 1, b = 1, c = -20
∆ = 1² - 4 * 1 * (-20) = 1 + 80 = 81
√∆ = 9
x = (-1 - 9)/2 = -5
x = (-1 + 9)/2 = 4
d)
f(x) = -x² - 4x + 12
a = -1, b = -4, c = 12
∆ = (-4)² - 4 * (-1) * 12 = 16 + 48 = 64
√∆ = 8
x = (4 - 8)/(-2) = 2
x = (4 + 8)/(-2) = -6